BIOETIKA PENELITIAN BIOEKOLOGI TUMBUHAN KETAPANG DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Fhina Marisya Putri; Fitriani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
and economic importance. The Beach Almond tree (Terminalia catappa) dominates the coastal vegetation in this region, serving as a natural windbreak, abrasion barrier, and shade. This study aims to analyze the bioecological characteristics of T. catappa while integrating bioethical principles into the research procedures. The methods employed include purposive sampling for ecological data collection and descriptive observation for bioethical aspects. The results indicate that the density of T. catappa at Kuranji Beach remains relatively stable, though it faces increasing anthropogenic pressures. The enforcement of research bioethics including the principle of non-maleficence toward the ecosystem and respect for local wisdom is essential for the sustainability of research activities in this area.